The determinants of conflict: North Korea's foreign policy choices, 1960-2011 - Wallace, Robert Daniel (Kansas State University, 2014)
North Korea and the ruling Kim regime continues to present a unique security dilemma to both East Asia and the international community. The Kim regime's actions, which often include hostile military and diplomatic foreign policy actions, often seem inconsistent with parallel efforts to peacefully engage the international community. This research examines the following question: what has been the historic relationship between North Korea’s domestic conditions and its propensity to engage in “hostile” diplomatic and military activities? I also consider whether the concept of diversionary theory, the idea that leaders pursue external conflict when faced with domestic problems, is an explanation for these actions. The study initially proposes there is a relationship between North Korea’s domestic challenges and its willingness to engage in conflict activities aimed primarily at South Korea and the United States. To test these ideas, I conduct a quantitative analysis of North Korean event data collected from both US and Korean sources from 1960-2011 and a qualitative analysis of three case studies. My findings provide only limited support to the idea that internal conditions faced by the Kim regime influence its conflict behavior. More influential are a select number of external conditions, especially those involving South Korea, which often prompt North Korean responses and heightened conflict levels. This research also finds that the ruling Kim regime has often turned to diversion-type actions as a means to achieve domestic goals, yet diversionary theory itself is insufficient to explain these activities. North Korea represents an ongoing security dilemma for both East Asia and the international community and in this study, I demonstrate how historical and political science methods can be used to examine and explain the actions of this reclusive state.
Keywords: Security studies; Diversionary theory; Conflict; History; North Korea; Political science; Military Studies (0750); Peace Studies (0563); Political Science (0615)